Method of Giving Learning Assignments and Recitations as an Effort to Improve Student Learning Outcomes at MIS An Nur Kabupaten Bandung - Munawaroh; Fadilah, Musrifatun (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to improve the learning of Islamic Religious Education (Fiqh Lessons) through the method of giving learning assignments and registration. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of Madrasah Ibtidaiyah. Data from the study were calculated using simple statistics, namely: 1) To assess repetition or formative tests and 2) For learning completeness, there are two categories of learning completeness, namely individually and classically. The results of the study showed that 1) Problem-based learning has a positive impact on improving student learning achievement which is indicated by an increase in student learning completeness in each cycle, namely cycle I (68.18%), cycle II (77.27%), cycle III (86.36%); 2) The application of the method of giving learning assignments and recitations has a positive influence, namely it can increase student learning motivation as indicated by the results of interviews with some students, the average student answer stated that students were interested and interested in the methods of giving learning assignments and recitations so that they became motivated to learn.